Chemical characterization, antibacterial, antibiofilm, and antioxidant activities of the methanolic extract of Paratapes undulatus clams (Born, 1778) - Mosad A. Ghareeb, Salwa A.H. Hamdi, Mona Fathi Fol, Amina M. Ibrahim (Journal of Applied Pharmaceutical Science, 2022)
Mollusks represent the second-largest animal phylum in the marine realm. They have direct and indirect commercial and medical importance worldwide. Paratapes undulatus is a species of saltwater clam, a marine bivalve mollusk in the family Veneridae. The current study aimed to examine the chemical profile of the methanolic extract of P. undulatus soft parts using Gas chromatography mass spectroscopy (GC-MS) analysis and then assessing its antibacterial, antibiofilm, and antioxidant activities. GC-MS investigations led to the identification of major components including 7-hexadecenoic acid, methyl ester, (Z) (32.01%), hexadecanoic acid, methyl ester (14.03%), 9-octadecenoic acid, methyl ester (8.43%), palmitoleic acid (5.75%), 5,8,11,14,17-eicosapentaenoic acid, methyl ester (5.25%), tridecanoic acid, 4,8,12-trimethyl-, methyl ester (3.44%), tetradecanoic acid, methyl ester (3.34%), and cis-9-hexadecenoic acid (3.23%). Moreover, the results revealed that the extract showed remarkable antibacterial, antibiofilm, and antioxidant activities. In conclusion, the present results might be helpful for pharmaceutical companies to develop natural supplements from these clams.
Keywords: Paratapes undulatus clams, antibacterial, antibiofilm, antioxidant, GC-MS